Chitosan fiber membrane as well as preparation method and application thereof

By optimizing the curing process of chitosan fiber membranes, using a curing solution dissolved in sodium hydroxide in aqueous ethanol for curing treatment, the biosafety risk problems caused by the use of toxic reagents in the prior art are solved, and the biocompatibility and cleaning convenience are improved.

CN119548661APending Publication Date: 2025-03-04JIHUA LAB +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411831047.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing chitosan fiber membranes require the use of highly toxic reagents during the preparation process, which poses biosafety risks.

Method used

By optimizing the curing process of chitosan fiber membranes, the curing liquid prepared by dissolving sodium hydroxide in aqueous ethanol is used for curing treatment, avoiding the use of highly toxic reagents and making the curing liquid easy to clean.

Benefits of technology

It realizes that no toxic reagents are used during the curing process, which ensures the biocompatibility of the chitosan fiber membrane and simplifies the cleaning process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119548661A_ABST
    Figure CN119548661A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biological materials, and discloses a chitosan fiber membrane and a preparation method and application thereof, and the preparation method comprises the following steps: (1) preparing a chitosan-containing fiber membrane through a spinning technology; (2) preparing a curing liquid: dissolving sodium hydroxide in an ethanol water solution with the volume concentration of 75% to prepare the curing liquid; and (3) carrying out curing treatment on the chitosan-containing fiber membrane: soaking the chitosan-containing fiber membrane in a curing liquid, then washing the chitosan-containing fiber membrane with water until the chitosan-containing fiber membrane is neutral, and drying the chitosan-containing fiber membrane at normal temperature to obtain the chitosan fiber membrane. By optimizing the curing process of the chitosan fiber membrane, a reagent with relatively strong toxicity does not need to be used in the curing process, and the curing liquid adopted in the curing process is also easy to clean and remove, so that the biocompatibility of the prepared chitosan fiber membrane can be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of biomaterials, and mainly to a chitosan fiber membrane and a preparation method and application thereof. Background Art

[0002] Refractory wounds are characterized by high morbidity, difficulty in treatment, and high risk, mainly including traumatic ulcers, diabetic foot, radiation damage, etc., which require intensive and long-term treatment with expensive products, which not only seriously increase the medical burden, but also reduce the quality of life of patients. Therefore, the development of functional dressings for refractory wounds has received extensive research attention. Wound dressings can greatly improve the wound healing microenvironment and are crucial to the healing process. However, existing wound dressings have problems such as single function, poor antibacterial performance and poor wound healing performance.

[0003] In recent years, electrospun nanofiber dressings have attracted extensive attention in the biomedical field due to their unique microstructure and biodegradability. Electrospun nanofibers have high porosity and high specific surface area. Their interconnected three-dimensional porous structure is similar to the natural extracellular matrix. They can not only effectively absorb wound exudate and enhance the penetration of nutrients and oxygen, but also effectively block bacterial infection and promote epidermal cell proliferation and migration. They have broad application prospects in the field of wound dressings.

[0004] Chitosan is a linear polymer material obtained by deacetylation of natural chitin. It is the only alkaline polymer polysaccharide with positive charge in nature. It has excellent biocompatibility, biodegradability, antibacterial, antioxidant, and wound healing properties, and is widely used in the field of medical dressings. In the prior art, chitosan fiber membranes are prepared by spinning technology. However, the prepared chitosan fiber membranes are often cross-linked and cured with glutaraldehyde, which is highly toxic and easily poses a biosafety risk.

[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a chitosan fiber membrane and a preparation method and application thereof, aiming to solve the problem that the existing chitosan fiber membrane has biosafety risks due to the need to use highly toxic reagents in the preparation process.

[0007] The technical solution of this application is as follows: A method for preparing a chitosan fiber membrane, comprising the following steps: (1) Preparation of chitosan-containing fiber membranes by spinning technology; (2) Preparation of curing liquid: Dissolving sodium hydroxide in an ethanol aqueous solution having a volume concentration of 75% to prepare the solidifying liquid; (3) Curing the fiber membrane containing chitosan: The fiber membrane containing chitosan is immersed in a solidifying liquid, then washed with water until neutral, and dried at room temperature to obtain a chitosan fiber membrane.

[0008] By optimizing the curing process of the chitosan fiber membrane, there is no need to use highly toxic reagents during the curing process, and the curing liquid used in the curing process is also easy to clean and remove, which can ensure the biocompatibility of the prepared chitosan fiber membrane.

[0009] The method for preparing the chitosan fiber membrane, wherein in step (3), the soaking time is at least 4 hours.

[0010] The purpose of soaking the fiber membrane in the solidifying liquid for at least 4 hours is to solidify the water-soluble chitosan-containing fiber membrane and stabilize its nanofiber structure so that it will not dissolve in water.

[0011] The method for preparing the chitosan fiber membrane, wherein in step (2), the mass concentration of the sodium hydroxide in the ethanol aqueous solution is 5wt%.

[0012] The method for preparing chitosan fiber membrane, wherein in step (1), the process of preparing the fiber membrane containing chitosan by spinning technology comprises the following steps: The electrospinning solution containing chitosan was used as the spinning solution, and the fiber membrane containing chitosan was prepared by electrospinning. The spinning parameters were set as follows: the positive electrode voltage was 15-20 kV, the negative electrode voltage was -3 kV, the spinning solution flow rate was 0.2-3 mL / h, the receiving distance was 10-25 cm, and the air humidity was 30-60%.

[0013] The method for preparing the chitosan fiber membrane, wherein the air humidity is 30%.

[0014] The method for preparing the chitosan fiber membrane, wherein the electrospinning solution containing chitosan is prepared by the following method: Chitosan was prepared by homogeneous deacetylation method: chitosan powder was evenly dispersed in sodium hydroxide crushed ice, stirred until the sodium hydroxide crushed ice was completely melted, and bubbles were removed by ultrasonication, and then frozen at -15°C to -30°C for 12 to 48 hours, and then taken out and thawed naturally; the chitosan solution was obtained by heating and stirring in a 25 to 60°C water bath for a homogeneous deacetylation reaction, and the reaction time was 6 to 48 hours to obtain a deacetylated chitosan solution; the deacetylated chitosan solution was poured into anhydrous ethanol for precipitation, and washed with an ethanol solution with a volume concentration of 80% until neutral, and freeze-dried to obtain the chitosan with a deacetylation degree of 20 to 70%; The chitosan is subjected to enzymatic hydrolysis treatment: the chitosan is dissolved in an acetic acid solution with a mass concentration of 1-2%, chitosanase is added, and the chitosan is stirred in a water bath at 25-60° C. for enzymatic hydrolysis for 0.5-4 h, so that the molecular weight range of the chitosan is 200-700 kDa; The electrospinning solution containing chitosan is prepared by dissolving the chitosan in an acetic acid solution having a mass concentration of 90%, wherein the mass concentration of the chitosan in the acetic acid solution is 2-12 wt%, to obtain the electrospinning solution containing chitosan.

[0015] The method for preparing chitosan fiber membrane, wherein the amount of chitosan powder added is 3-6 g of chitosan powder per 600 mL of sodium hydroxide crushed ice; The mass concentration of sodium hydroxide in the sodium hydroxide crushed ice is 5-40 wt %; The amount of anhydrous ethanol used is 4 times the volume of the deacetylated chitosan solution; Every 0.5-2 g of the chitosan is dissolved in 100 mL of the acetic acid solution having a mass concentration of 1-2%.

[0016] The method for preparing the chitosan fiber membrane, wherein, in the step of preparing the electrospinning solution containing chitosan, when the molecular weight of the chitosan is 690 kDa, the mass concentration of the chitosan in the acetic acid solution is 4~5 wt%, and when the molecular weight of the chitosan is 340 kDa, the mass concentration of the chitosan in the acetic acid solution is 9~11 wt%.

[0017] A chitosan fiber membrane is prepared by the above-mentioned method for preparing chitosan fiber membrane.

[0018] An application of the chitosan fiber membrane as described above, wherein the chitosan fiber membrane is used to prepare a wound dressing.

[0019] Beneficial effects: The preparation method of the chitosan fiber membrane of the present application optimizes the curing process of the chitosan fiber membrane, and does not need to use highly toxic reagents during the curing process. In addition, the curing liquid used in the curing process is also easy to clean and remove, which can ensure the biocompatibility of the prepared chitosan fiber membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscope image of the chitosan fiber membrane prepared in Example 1 of the present application.

[0021] Figure 2 This is a scanning electron microscope image of the chitosan fiber membrane prepared in Example 2 of the present application.

[0022] Figure 3 This is a graph showing the cytotoxicity test results of the chitosan fiber membranes prepared in Examples 1-3 of the present application and the comparative example. DETAILED DESCRIPTION

[0023] The present application provides a chitosan fiber membrane and a preparation method and application thereof. To make the purpose, technical solution and effect of the present application clearer and more specific, the present application is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0024] The present application provides a method for preparing a chitosan fiber membrane, comprising the following steps: (1) Preparation of chitosan-containing fiber membranes by spinning technology.

[0025] In step (1), the fiber membrane containing chitosan can be prepared by electrospinning, wet spinning, dry-wet spinning, etc.

[0026] In the embodiment scheme of the present application, the preparation of fiber membrane containing chitosan by electrospinning is taken as an example to illustrate the scheme of the present application, but the preparation method of chitosan fiber membrane of the present application is applicable to fiber membrane of chitosan system.

[0027] Specifically, in step (1), the process of preparing a fiber membrane containing chitosan by spinning technology includes the following steps: The electrospinning solution containing chitosan was used as the spinning solution, and the fiber membrane containing chitosan was prepared by electrospinning. The spinning parameters were set as follows: positive electrode voltage was 15-20 kV, negative electrode voltage was -3 kV, spinning solution flow rate was 0.2-3 mL / h, receiving distance was 10-25 cm, and air humidity was 30-60%.

[0028] In step (1), the air humidity is preferably 30%. The fiber morphology of the fiber membrane containing chitosan produced under this air humidity is better.

[0029] (2) Preparation of curing liquid: The solidifying liquid is prepared by dissolving sodium hydroxide in an ethanol aqueous solution with a volume concentration of 75%, and the mass concentration of the sodium hydroxide in the ethanol aqueous solution is 5 wt %.

[0030] Since chitosan has a high solubility under acidic conditions, acetic acid is used as a common solvent in the existing preparation process of chitosan-containing fiber membranes to help dissolve chitosan and form a uniform spinning solution, thereby ensuring the quality and performance of the fiber. Therefore, most chitosan-containing fiber membranes contain acetic acid, and the curing of this application is mainly aimed at chitosan-containing fiber membranes prepared using acetic acid as a solvent.

[0031] The solidifying liquid of the present application can neutralize the excess acetic acid in the spinning solution and cause the conformational change of the chitosan molecular chain to form a stable nanofiber structure. The solidifying liquid itself can also be easily removed through a subsequent water washing process to ensure the biocompatibility of the prepared chitosan fiber membrane.

[0032] (3) Curing the fiber membrane containing chitosan: The fiber membrane containing chitosan is immersed in a curing liquid for at least 4 hours, then washed with water until neutral, and dried at room temperature to obtain a chitosan fiber membrane.

[0033] In step (3), the fiber membrane containing water-soluble chitosan is solidified by immersing it in the solidification liquid for at least 4 hours, so as to stabilize its nanofiber structure and make it insoluble in water.

[0034] In the present application, by optimizing the curing process of the chitosan fiber membrane, there is no need to use highly toxic reagents during the curing process, and the curing liquid used in the curing process is also easy to clean and remove, thereby ensuring the biocompatibility of the prepared chitosan fiber membrane.

[0035] Due to the problems of low solubility of chitosan, high solution viscosity, and electrostatic repulsion of molecular chains under high voltage electric fields, the morphology of chitosan nanofibers prepared by spinning technology in the prior art needs to be improved. Therefore, in the present application, the electrospinning solution containing chitosan is preferably prepared by the following method: (a) Chitosan was prepared by homogeneous deacetylation method: The chitosan powder was evenly dispersed in sodium hydroxide crushed ice (NaOH mass concentration was 5-40 wt%), stirred until the sodium hydroxide crushed ice was completely melted, and after removing bubbles by ultrasonic, it was frozen at -15℃~-30℃ for 12-48 h, and then taken out and thawed naturally; The chitosan solution was obtained by heating and stirring in a water bath at 25-60°C for homogeneous deacetylation for 6-48 hours. The deacetylated chitosan solution was poured into 4 times the volume of anhydrous ethanol for precipitation, washed with an ethanol solution with a volume concentration of 80% until neutral, and freeze-dried to obtain chitosan with a deacetylation degree of 20-70%.

[0036] In step (a), the amount of chitosan powder added can be 3 to 6 g of chitosan powder per 600 mL of sodium hydroxide crushed ice. Through multiple experiments, it has been verified that the above ratio can ensure that the chitosan can be completely dissolved after the NaOH crushed ice and a subsequent freeze-thaw cycle. If the amount of chitosan added is too much, the number of subsequent freeze-thaw cycles needs to be increased, which takes more time. The step of dissolving the chitosan powder is also optimized in this application. The sodium hydroxide solution is frozen into sodium hydroxide crushed ice and then crushed into crushed ice, and the chitosan powder is directly dispersed in the sodium hydroxide crushed ice. This can make the temperature of the entire reaction system uniform and ensure that the chitosan is evenly dissolved.

[0037] In step (a), the degree of deacetylation can be controlled by controlling the reaction time. Generally speaking, a reaction time of 8 h corresponds to a deacetylation degree of 28%, a reaction time of 16 h corresponds to a deacetylation degree of 51%, and a reaction time of 24 h corresponds to a deacetylation degree of 63%.

[0038] (b) Enzymatic hydrolysis of chitosan: The chitosan prepared in step (a) is dissolved in an acetic acid solution having a mass concentration of 1-2%, and then chitosanase is added, and the mixture is stirred in a water bath at 25-60° C. for enzymolysis for 0.5-4 h to obtain chitosan with a molecular weight range (weight average molecular weight) of 200-700 kDa.

[0039] In step (b), the viscosity and reaction rate of the reaction system are adjusted to a moderate level by optimizing the concentration of chitosan in the acetic acid solution and the amount of chitosanase added, thereby making the molecular weight highly controllable.

[0040] Specifically, every 0.5-2 g of chitosan can be dissolved in 100 mL of acetic acid solution with a mass concentration of 1-2%. The advantage of using the above ratio is that the viscosity of the chitosan after dissolution is moderate, and it can be easily stirred in the early stage of enzyme degradation, which is conducive to ensuring the uniformity of the reaction system. If the viscosity is too high, it will be difficult to stir, which will make the reaction system prone to unevenness, resulting in a wider molecular weight distribution of chitosan.

[0041] Specifically, 2-10 mg chitosanase can be added to every 1g chitosan. The amount of chitosanase added is based on the reaction speed. This addition ratio can make the reaction milder and obtain parameters of different molecular weights in a short time. If the amount added is small, the degradation rate is slow, which will greatly extend the reaction time. If the amount added is too much, the degradation rate will be too fast, the uniformity of the reaction will be reduced, the reaction time will be short, and it will be difficult to collect chitosan of different molecular weights.

[0042] In step (b), the molecular weight of the prepared chitosan is mainly controlled by controlling the enzymatic hydrolysis time. The longer the reaction time, the lower the molecular weight.

[0043] (c) Preparation of electrospinning solution containing chitosan: Chitosan was dissolved in an acetic acid solution with a mass concentration of 90%, and the mass concentration of chitosan in the acetic acid solution was 2-12 wt%, to obtain an electrospinning solution containing chitosan.

[0044] For chitosan raw materials in the above molecular weight range and deacetylation degree range, the mass concentration of chitosan in the electrospinning solution containing chitosan is 2~12 wt%, which can ensure that the electrospinning solution containing chitosan has spinnability. Chitosans of different molecular weights correspond to different optimal concentrations, and the smaller the molecular weight, the higher the optimal concentration. For example, for chitosan raw materials with a molecular weight of 690 kDa, the preferred concentration is 4~5 wt%, and for chitosan raw materials with a molecular weight of 340 kDa, the preferred concentration is 9~11 wt%.

[0045] In the present application, a chitosan fiber membrane is also provided, which is prepared by the above-mentioned method for preparing the chitosan fiber membrane.

[0046] In the present application scheme, the application of the chitosan fiber membrane is also provided, and the chitosan fiber membrane is used to prepare wound dressing.

[0047] The preparation method of the electrospinning solution containing chitosan can reduce its crystallinity and intermolecular interaction by reducing the deacetylation degree and molecular weight of chitosan, without any additive addition, and can realize the preparation of pure chitosan fiber membrane, and further ensure the biocompatibility of the prepared chitosan fiber membrane. In addition, by using chitosan with low deacetylation degree and low molecular weight as spinning raw material, the chitosan fiber membrane constructed by electrospinning technology not only retains the biological activity of chitosan, but also has a structure similar to the extracellular matrix, which can promote epidermal cell proliferation and migration, and the antibacterial properties of chitosan itself and the physical barrier effect provided by the nanofiber membrane can provide double protection for the wound surface, while ensuring the air permeability of the wound dressing. In addition, chitosan with a deacetylation degree of about 50% greatly increases the hydrophilicity of nanofibers due to its low crystallinity and interchain hydrogen bonds, which is more conducive to the absorption of wound exudate and accelerates the migration speed of epidermal cells, and is an ideal wound dressing material.

[0048] In the present application, pure chitosan fiber membrane refers to a membrane that does not contain other flexible water-soluble polymers. However, in the above-mentioned preparation method of chitosan fiber membrane, chitosanase is basically removed during the chitosan raw material sedimentation and washing process, and acetic acid is also removed during the curing process in the above-mentioned preparation method of chitosan fiber membrane. Therefore, in addition to not containing other flexible water-soluble polymers, the chitosan fiber membrane of the present application also basically does not contain chitosanase and acetic acid, so that the prepared pure chitosan fiber membrane can better exert the biological activity of chitosan.

[0049] The present application is further described below through specific embodiments.

[0050] Embodiment 1: (1) Electrospinning solution containing chitosan: 4.5 g chitosan powder was evenly dispersed in 600 mL sodium hydroxide crushed ice (NaOH mass concentration was 15 wt%), stirred until the sodium hydroxide crushed ice was completely melted, and bubbles were removed by ultrasound (ultrasonic power was 500 W, ultrasonic time was 5 min), and then frozen at -20℃ for 24 h, and taken out to thaw naturally. Then, it was heated and stirred in a 40℃ water bath for homogeneous deacetylation reaction, and the reaction time was 16 h. Then, the deacetylated chitosan solution was poured into 4 times the volume of anhydrous ethanol for precipitation, washed with 80% volume ethanol solution until neutral, and freeze-dried to obtain chitosan with a deacetylation degree of 51%. 1 g chitosan was dissolved in 100 mL 1% acetic acid solution, and then 5 mg chitosanase was added. The chitosan was hydrolyzed by stirring in a 40℃ water bath for 1.5 h. The weight average molecular weight of chitosan was 340 kDa. The chitosan was dissolved in an acetic acid solution having a mass concentration of 90% to a mass concentration of 10 wt%.

[0051] (2) Preparation of fiber membrane containing chitosan: Chitosan fiber membrane was prepared by electrospinning. The spinning conditions were as follows: positive electrode voltage of 18 kV, negative electrode voltage of -3 kV, spinning solution flow rate of 0.8 ml / h, receiving distance of 20 cm, and air humidity of 50%.

[0052] (3) Preparing a solidifying liquid: dissolving sodium hydroxide in an ethanol aqueous solution with a volume concentration of 75% to prepare a solidifying liquid, wherein the mass concentration of sodium hydroxide in the ethanol aqueous solution is 5 wt %.

[0053] (4) Curing treatment: The fiber membrane containing chitosan is immersed in a curing solution for 4 h, then washed with water until neutral, and dried at room temperature to obtain a chitosan fiber membrane.

[0054] Example 2: (The main difference from Example 1 is the difference in air humidity) (1) Electrospinning solution containing chitosan: 4.5 g chitosan powder was evenly dispersed in 600 mL sodium hydroxide crushed ice (NaOH mass concentration was 15 wt%), stirred until the sodium hydroxide crushed ice was completely melted, and bubbles were removed by ultrasound (ultrasonic power was 500 W, ultrasonic time was 5 min), and then frozen at -20℃ for 24 h, and taken out to thaw naturally. Then, it was heated and stirred in a 40℃ water bath for homogeneous deacetylation reaction, and the reaction time was 16 h. Then, the deacetylated chitosan solution was poured into 4 times the volume of anhydrous ethanol for precipitation, washed with 80% volume ethanol solution until neutral, and freeze-dried to obtain chitosan with a deacetylation degree of 51%. 1 g chitosan was dissolved in 100 mL 1% acetic acid solution, and then 5 mg chitosanase was added. The chitosan was hydrolyzed by stirring in a 40℃ water bath for 1.5 h. The weight average molecular weight of chitosan was 340 kDa. The chitosan was dissolved in an acetic acid solution having a mass concentration of 90% to a mass concentration of 10 wt%.

[0055] (2) Preparation of fiber membrane containing chitosan: Chitosan fiber membrane was prepared by electrospinning. The spinning conditions were as follows: positive electrode voltage of 18 kV, negative electrode voltage of -3 kV, spinning solution flow rate of 0.8 ml / h, receiving distance of 20 cm, and air humidity of 30%.

[0056] (3) Preparing a solidifying liquid: dissolving sodium hydroxide in an ethanol aqueous solution with a volume concentration of 75% to prepare a solidifying liquid, wherein the mass concentration of sodium hydroxide in the ethanol aqueous solution is 5 wt %.

[0057] (4) Curing treatment: The fiber membrane containing chitosan is immersed in a curing solution for 4 h, then washed with water until neutral, and dried at room temperature to obtain a chitosan fiber membrane.

[0058] In Example 2, the molecular weight of chitosan is reduced by enzymatic hydrolysis, and the concentration of the spinning solution is increased, so that the prepared nanofibers have a uniform morphology.

[0059] Figure 1-2 The following are scanning electron microscope images of the chitosan fiber membranes prepared in Examples 1-2. Figure 1 It can be seen that the chitosan fiber membrane has a clear nanofiber structure and the nanofiber morphology is uniform. Example 2 was prepared under low air humidity conditions. Figure 2 It can be seen that there is a clear nanofiber structure without beading, indicating good spinning performance.

[0060] Example 3 (1) Electrospinning solution containing chitosan: Chitosan (degree of deacetylation > 90%) and PEO (polyethylene oxide) were dissolved in a 52% formic acid aqueous solution, the mass concentration of chitosan in the formic acid aqueous solution was 2%, and the mass concentration of EPO in the formic acid aqueous solution was 0.3%. The solution was stirred magnetically until it was uniform.

[0061] (2) Preparation of fiber membrane containing chitosan: Chitosan fiber membrane was prepared by electrospinning. The spinning conditions were as follows: positive electrode voltage of 10 kV, negative electrode voltage of -3 kV, spinning solution flow rate of 0.5 ml / h, receiving distance of 10 cm, and air humidity of 30%.

[0062] (3) Preparing a solidifying liquid: dissolving sodium hydroxide in an ethanol aqueous solution with a volume concentration of 75% to prepare a solidifying liquid, wherein the mass concentration of sodium hydroxide in the ethanol aqueous solution is 5 wt %.

[0063] (4) Curing treatment: The fiber membrane containing chitosan is immersed in a curing solution for 4 h, then washed with water until neutral, and dried at room temperature to obtain a chitosan fiber membrane.

[0064] The difference from Example 1 is that the chitosan fiber membrane is prepared by using other existing spinning solutions. It can be seen from this example that the chitosan fiber membrane prepared by the existing chitosan-containing spinning solution is also suitable for the curing process of the present application.

[0065] Comparative Example (the main difference from Example 2 is the different curing method) (1) Electrospinning solution containing chitosan: 4.5 g chitosan powder was evenly dispersed in 600 mL sodium hydroxide crushed ice (NaOH mass concentration was 15 wt%), stirred until the sodium hydroxide crushed ice was completely melted, and bubbles were removed by ultrasound (ultrasonic power was 500 W, ultrasonic time was 5 min), and then frozen at -20℃ for 24 h, and taken out to thaw naturally. Then, it was heated and stirred in a 40℃ water bath for homogeneous deacetylation reaction, and the reaction time was 16 h. Then, the deacetylated chitosan solution was poured into 4 times the volume of anhydrous ethanol for precipitation, washed with 80% volume ethanol solution until neutral, and freeze-dried to obtain chitosan with a deacetylation degree of 51%. 1 g chitosan was dissolved in 100 mL 1% acetic acid solution, and then 5 mg chitosanase was added. The chitosan was hydrolyzed by stirring in a 40℃ water bath for 1.5 h. The weight average molecular weight of chitosan was 340 kDa. The chitosan was dissolved in an acetic acid solution having a mass concentration of 90% to a mass concentration of 10 wt%.

[0066] (2) Preparation of fiber membrane containing chitosan: Chitosan fiber membrane was prepared by electrospinning. The spinning conditions were as follows: positive electrode voltage of 18 kV, negative electrode voltage of -3 kV, spinning solution flow rate of 0.8 ml / h, receiving distance of 20 cm, and air humidity of 30%.

[0067] (3) Preparation of curing solution: Prepare a 0.2% (w / v) glutaraldehyde solution using isopropanol as the solvent.

[0068] (4) Curing treatment: The fiber membrane containing chitosan is immersed in a curing solution for 4 h, then washed with water and dried at room temperature to obtain a chitosan fiber membrane.

[0069] The chitosan fiber membranes prepared in Examples 1-3 and the comparative example were subjected to cytotoxicity tests. The cytotoxicity test method was to test the cytotoxicity of the chitosan fiber membranes using a direct contact method: L929 cells were cultured in a culture medium (DMEM) supplemented with 10% fetal bovine serum and 1% penicillin-streptomycin solution; chitosan fiber membranes prepared in Examples 1-3 and the comparative example with a diameter of 1 cm were added to a 24-well plate, and then L929 cells were inoculated on the surface of the chitosan fiber membrane at a density of 80,000 cells per well, and the 24-well plate was placed in a humidified atmosphere of 37° C. and 5% CO2 for culture, and the control group was a standard culture medium; after culturing for 24 hours, a culture medium supplemented with 10% CCK-8 reagent was added to each well, and the culture was continued for another 2 hours, and the absorbance of each well at 450 nm was recorded using a microplate reader (Bio-Tek ELx800, USA).

[0070] Cytotoxicity test results Figure 3 As shown, from Figure 3 It can be seen that the cell activity of the chitosan fiber membranes of Examples 1-3 is all greater than 80%, indicating that the chitosan fiber membranes prepared in Examples 1-3 have excellent biocompatibility; while the cell activity of the chitosan fiber membrane of the comparative example is about 70%, indicating that glutaraldehyde curing will cause certain residues and there is a risk of cytotoxicity.

[0071] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made according to the above description, and all these improvements and changes should fall within the scope of protection of the present application.

Claims

1. A method for preparing a chitosan fiber membrane, characterized in that: The following steps are involved: (1) Preparation of chitosan-containing fiber membranes by spinning technology; (2) Preparation of curing liquid: Dissolving sodium hydroxide in an ethanol aqueous solution having a volume concentration of 75% to prepare the solidifying liquid; (3) Curing the fiber membrane containing chitosan: The fiber membrane containing chitosan is immersed in a solidifying liquid, then washed with water until neutral, and dried at room temperature to obtain a chitosan fiber membrane.

2. The method for preparing chitosan fiber membrane according to claim 1, characterized in that: In step (3), the soaking time is at least 4 hours.

3. The method for preparing chitosan fiber membrane according to claim 1, characterized in that: In step (2), the mass concentration of the sodium hydroxide in the ethanol aqueous solution is 5 wt %.

4. The method for preparing chitosan fiber membrane according to claim 1, characterized in that: In step (1), the process of preparing a fiber membrane containing chitosan by spinning technology includes the following steps: The electrospinning solution containing chitosan was used as the spinning solution, and the fiber membrane containing chitosan was prepared by electrospinning. The spinning parameters were set as follows: the positive electrode voltage was 15-20 kV, the negative electrode voltage was -3 kV, the spinning solution flow rate was 0.2-3 mL / h, the receiving distance was 10-25 cm, and the air humidity was 30-60%.

5. The method for preparing chitosan fiber membrane according to claim 4, characterized in that: The air humidity is 30%.

6. The method for preparing chitosan fiber membrane according to claim 4, characterized in that: The electrospinning solution containing chitosan is prepared by the following method: Chitosan was prepared by homogeneous deacetylation method: chitosan powder was evenly dispersed in sodium hydroxide crushed ice, stirred until the sodium hydroxide crushed ice was completely melted, and bubbles were removed by ultrasonication, and then frozen at -15°C to -30°C for 12 to 48 hours, and then taken out and thawed naturally; the chitosan solution was obtained by heating and stirring in a 25 to 60°C water bath for a homogeneous deacetylation reaction, and the reaction time was 6 to 48 hours to obtain a deacetylated chitosan solution; the deacetylated chitosan solution was poured into anhydrous ethanol for precipitation, and washed with an ethanol solution with a volume concentration of 80% until neutral, and freeze-dried to obtain the chitosan with a deacetylation degree of 20 to 70%; The chitosan is subjected to enzymatic hydrolysis treatment: the chitosan is dissolved in an acetic acid solution with a mass concentration of 1-2%, chitosanase is added, and the chitosan is stirred in a water bath at 25-60° C. for enzymatic hydrolysis for 0.5-4 h, so that the molecular weight range of the chitosan is 200-700 kDa; The electrospinning solution containing chitosan is prepared by dissolving the chitosan in an acetic acid solution having a mass concentration of 90%, wherein the mass concentration of the chitosan in the acetic acid solution is 2-12 wt%, to obtain the electrospinning solution containing chitosan.

7. The method for preparing chitosan fiber membrane according to claim 6, characterized in that: The chitosan powder is added in an amount of 3 to 6 g per 600 mL of sodium hydroxide crushed ice; The mass concentration of sodium hydroxide in the sodium hydroxide crushed ice is 5-40 wt %; The amount of anhydrous ethanol used is 4 times the volume of the deacetylated chitosan solution; Every 0.5-2 g of the chitosan is dissolved in 100 mL of the acetic acid solution having a mass concentration of 1-2%.

8. The method for preparing chitosan fiber membrane according to claim 6, characterized in that: In the step of preparing the electrospinning solution containing chitosan, when the molecular weight of the chitosan is 690 kDa, the mass concentration of the chitosan in the acetic acid solution is 4-5 wt%, and when the molecular weight of the chitosan is 340 kDa, the mass concentration of the chitosan in the acetic acid solution is 9-11 wt%.

9. A chitosan fiber membrane, characterized in that: The chitosan fiber membrane is prepared by the preparation method of the chitosan fiber membrane according to any one of claims 1 to 8.

10. An application of the chitosan fiber membrane as claimed in claim 9, characterized in that: The chitosan fiber membrane is used to prepare wound dressing.

Citation Information

Cited By

  • Chitosan electrostatic spinning solution and preparation method thereof

    CN119531010A

  • Chitosan electrospinning liquid and preparation method thereof

    CN119531010B